RANCANG BANGUN SISTEM PEMESANAN TIKET PESAWAT BERBASIS WEB - Hakim, Arief Rachman; Baihaqi, Wiga Maulana (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2023)
Indonesia is the largest archipelagic country in the world which has very strategic geography. This can bring many opportunities in exploring natural riches and environmental services. For this reason, the existence of reliable and efficient transportation is very important. One means of transportation that is very popular and widely used by the public is airplanes. In this case, aircraft have made a significant contribution in supporting global connectivity, tourism and economic growth in various sectors. Even though airplane transportation has various advantages, there are still shortcomings in the airplane ticket purchasing process which still relies heavily on travel agents or direct purchases through the destination airline. This often causes problems, such as unstable ticket prices and concerns regarding the security of the ticket purchasing process. One innovation that can be a solution to the problem of purchasing plane tickets is the development of an application that provides a platform for purchasing plane tickets from various airlines. This application will combine various ticket options from various airlines on one platform. Apart from that, the application will also ensure the safety and security of passengers by providing the latest information about the availability of facilities on the plane and payment methods that are familiar to users. Thus, this application will provide convenience, comfort and security for prospective passengers in purchasing airline tickets of their choice.